Adolescent Decadency as An Implication of Online Games (Case Study on Teenagers Online Gamers) - Muhammad Nuzurul Qalam (The Magister of Islamic Education IAIN Pontianak, 2023)
The background of this research is today’s technological developments which are used by a handful of teenagers which then have implications for behavior. Teenage dominance is the main aspect of smartphone use. This is a challenge in itself to pay attention to the implications arising from online games. The purpose of this research is to raise awareness of the negative behavior caused by online games. This research was conducted through a qualitative approach, using the case study method. The research begins with observation, field notes, then continues with analysis. From the analysis of this study produces aspects that show the decadence of adolescent morals caused by online games. First, the excessive actions of teenagers that cause them to become addicted. Second, toxic utterances are often used when playing online games which are then carried around when carrying out other social activities. Therefore, it is necessary to strengthen morals by increasing faith in Allah SWT to fortify oneself from this culture that has eroded morals, so that one is aware of the importance of human relations (habluminannas). AbstrakLatar belakang penelitian ini adalah perkembangan teknologi di masa kini yang dimanfaatkan segelintir remaja yang kemudian berimplikasi terhadap perilaku. Dominan remaja menjadi aspek utama pada penggunaan smartphone. Hal ini menjadi tantangan tersendiri untuk memperhatikan implikasi yang ditimbulkan dari game online. Tujuan penelitian ini adalah untuk memberi kesadaran akan perilaku negatif yang disebabkan game online. Penelitian ini dilakukan melalui pendekatan kualitatif, dengan metode studi kasus. Penelitian diawali dengan observasi, catatan lapangan, kemudian dilanjutkan dengan analisis. Dari analisis penelitian ini menghasilkan aspek yang menunjukan dekadensi akhlak remaja yang disebabkan game online. Pertama, tindakan yang berlebih-lebihan remaja yang menyebabkan menjadi kecanduan. Kedua, ucapan toxic sering digunakan saat bermain game online yang kemudian dibawa-bawa tatkala melakukan aktivitas sosial lainnya. Maka dari itu, perlunya menguatkan akhlak dengan meningkatkan keimanan kepada Allah SWT untuk membentengi diri dari budaya yang sudah mengikis moral ini, sehingga sadar akan pentingnya hubungan sesama manusia (habluminannas). Kata kunci: Dekadensi akhlak, Implikasi game online, Penguatan akhlak